UNIVERSITY REFORM TODAY (4TH EDITION, REVISED) - MARGA, Andrei (2008)
Today education is a pre-condition of the achievements of individuals and communities. Therefore, serious reflection upon education nowadays has a larger impact than ever before. Additionally, the countries in South-Eastern Europe must break the vicious circle in which reforms are postponed because the educational premises, which in turn depend on economic and administrative reforms, are not met. The only way out is to accelerate the reform of education, an imperative action which requires conceptual clarifications, well elaborated programmes, and effective systematic changes. Petty politics of any colour is against a healthy reform of education (…)Note to the forth edition: This edition, which is going to be the last one, incorporates texts written until 2004. Together they express the author’s view on the university reform of the period.